Tinjauan Keakuratan Kode External Cause Diagnosis Cedera Kepala Berdasarkan ICD-10 Pada Rekam Medis Pasien Rawat Inap Di RSUP Dr. Soeradji Tirtonegoro - Ninawati; Reza Widiantoro; Astri Sri Wariyanti (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2023)
A preliminary survey was conducted, showing that 10 out of 10 external code medical records for the diagnosis of head injuries were inaccurate. The purpose of this study was to determine the accuracy of the external cause code for diagnosing head injuries based on the ICD-10 in the medical records of inpatients at dr. Soeradji Tirtonegoro. The research type was descriptive, with a retrospective approach. The study was conducted in the filing room. Time in May 2018. The total population of medical records for inpatients diagnosed with head injuries was 175 medical records. The sample size is 44 documents, with a systematic sampling technique. The instruments used were checklists, questionnaires, and observation guidelines. How to collect data from unstructured interviews and observation. Data analysis is descriptive in nature. The results of accuracy of the code external causes a diagnosis of head injury from 44 medical record documents 100% inaccurate code. Inaccuracy is incorrect code, there are 17 cases (39%) and there is incorect 5 categories code as many as 27 cases (61%). The conclusion is that inaccuracies occur because the officer has not carried out the inclusion and exclusion guidelines on the selected code, or the bottom of a chapter, block, category, or sub category in determining the selected code, directly coding without looking at the ICD when getting external cause information that often appear, and officers do not carry out coding up to 5 character digits because the standard for coding in hospitals is 15 minutes and officers still have to do an analysis of the completeness of medical records, code for claims, code in medical records, and still input into a computer.